A study of clinical and investigational profile of hirsute women at a tertiary care center in Western India - Priyanka G Dhanotia; Bela J Shah; Suyog S Dhamale (Wolters Kluwer Medknow Publications, 2020)
Background: Hirsutism is defined as a male pattern of hair distribution in a female. The interplay of androgens as well as other non androgenic hormones has an important role in the causation of hirsutism. Objectives: The objective of this study was to investigate the prevalent causes for hirsutism and to study the clinical profile of patients presenting with hirsutism. Methodology: Patients who came with features of hirsutism were screened by the modified Ferriman-Gallwey (mFG) scale and those with mFG ≥8 were included in the study. Patient's clinical history, family history, body mass index, general examination, dermatological examination, and systemic examination were carried out. Serum total testosterone, serum luteinizing hormone (LH), follicle-stimulating hormone (FSH), LH: FSH ratio, dehydroepiandrosterone sulfate (DHEAS), thyroid-stimulating hormone, blood sugar levels (fasting and postprandial), and abdomino-pelvic ultrasound were performed for all patients. Serum prolactin, free testosterone, 17 hydroxyprogesterone, T3level, T4level, serum cortisol level, and serum fasting insulin levels were performed in selected patients depending on the clinical scenario. Results: A total of 44 patients were studied during the study. About 95.45% of patients were categorized under mild mFG, whereas 4.55% of patients had moderate mFG score. Idiopathic hirsutism (IH) was the most common cause in our patients which accounted for 43.18% of patients followed by polycystic ovarian syndrome (PCOS) which was the reason for hirsutism in 38.64% of patients. Total testosterone was raised in 25% of patients. Free testosterone levels were performed for 25 patients and found to be raised in six patients. Five patients had elevated DHEAS levels of which four had PCOS and one had late-onset congenital adrenal hyperplasia. Conclusion: IH was the most common cause of hirsutism in our patients which was followed by PCOS.